The Effects of Online Learning Experience During the COVID-19 Pandemic on Students’ Satisfaction, Adjustment, Performance, and Loyalty : Evidence from Poland - Wilczewski, Michał; Gorbaniuk, Oleg; Mughan, Terry; Wilczewska, Ewelina (Journal of International Students, 2021)
This research investigates the student online learning experience (SOLE) during the 2020 spring Covid-19 pandemic. We collected quantitative data through an online survey from 362 international and 488 domestic students at a large Polish University. Correlation and path analysis within a conceptual model of SOLE and its academic outcomes established that (1) SOLE explained adjustment, performance, satisfaction, and loyalty, (2) academic adjustment predicts performance, satisfaction, and loyalty, (3) that academic performance and satisfaction predict student loyalty, and (4) that academic performance predicts satisfaction. Interestingly, time spent in quarantine/self-isolation did not exert any effect on academic outcomes in SOLE. Moreover, qualitative data collected via narrative interviews with 13 international and domestic students developed our understanding of SOLE and its outcomes. We propose some research and practice implications for universities to enhance SOLE.